2019
DOI: 10.1101/541326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The IDH-Tau-EGFR triad defines diffuse glioma pathology by controlling mesenchymal differentiation and neo-vascular fitness

Abstract: One Sentence SummaryTau, which is induced by IDH mutations, inhibits the EGFR/NF-kB/TAZ axis and impairs the mesenchymal/pericyte-like transformation of glioma cells, normalizing the vasculature and impairing tumor aggressiveness. AbstractMutant IDH1/2 gliomas represent a more indolent form of cancer. However, how this group of tumors evolve, in a microenvironment-dependent manner, is still a pending question. Here we describe that the expression of Tau, a gene classically associated with neurodegenerative dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 115 publications
2
3
0
Order By: Relevance
“…Nevertheless, to date it was unknown if different genetic alterations could modulate this transdiferentation process. Results from this study and our recently published data [7] suggest that it is governed by the EGFR/BMX signaling pathway.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Nevertheless, to date it was unknown if different genetic alterations could modulate this transdiferentation process. Results from this study and our recently published data [7] suggest that it is governed by the EGFR/BMX signaling pathway.…”
Section: Discussionsupporting
confidence: 77%
“…IF and IHC staining was performed as previously described [7] using primary and secondary antibodies described in Table S2. For quantification, slides were scanned at 63X or 40X magnification.…”
Section: Inmunofluorescent (If) and Inmunohistochemical (Ihc) Staining And Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…SVZ-EGFRvIII tumors showed a highly compact growth, whereas in SVZ-EGFRwt/amp tumors cells appeared detached from each other and from the tumor vessels ( Figure 5A). It has been shown that pericytic functions can be performed by the highly plastic glioma stem cells, which acquire mesenchymal and mural cell features (3) in a process regulated by EGFR signaling (6). In agreement with these notions, some tumor cells expressed αSMA in both SVZ glioma models ( Figure 5B).…”
Section: Glioma Derived-pericytes Stabilize the Vasculature In Egfrmusupporting
confidence: 75%
“…IDH mutant (IDHmut) gliomas have smaller BVs and are associated with less hypoxia compared with their wild-type (wt) counterparts (5). Moreover, we have recently described that the microtubule stabilizer TAU/MAPT is induced in IDHmut gliomas and promotes vascular normalization by opposing EGFR signaling (6).…”
mentioning
confidence: 99%